A Malay Muslim woman's travel narrative - Omar, Haslina (Asia Pacific Institute of Advanced Research, 2015)
This paper seeks to answer the call of autobiography scholars like Sidonie Smith and Julia Watson in working towards redressing inattentiveness towards women’s life narratives. It also will contribute to ongoing research done by historians like Siobhan Lambert-Hurley and her team of researchers in studying Muslim women’s autobiographical modes of writing. This paper examines one of the very few travel narratives to be published by a Malaysian Muslim woman. This particular mode of autobiographical writing has a long history back from the time of the Greeks and Romans. The publication of women’s personal narratives in the form of travel anecdotes such as A Call to Travel: Muslim Odysseys (2014) by Rumaizah Abu Bakar evidence the assertion by Borelli (2002) that women’s lives are of interest and value to the wider society and in telling their stories they perform an act that Susan Bosak (2015) says is “fundamental to what it is to be human.” Psychologists in the area of personality psychology have observed that life narratives written by highly generative adults reveal a strong concern for and commitment towards improving and maintaining the quality of life for future generations. Literary and psychological perspectives are taken in this study to examine how autobiographies in the form of travel narratives can function as a possible generative tool.